Anode for lithium secondary battery, method for producing anode for lithium secondary battery, and lithium secondary battery including anode

JP2025506005AActive Publication Date: 2025-03-05LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024546463
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-19
Filing Date
2023-10-20
Publication Date
2025-03-05
Estimated Expiration
2043-10-20

AI Technical Summary

Benefits of technology

【0019】 本発明の一実施態様によるリチウム二次電池用負極は、第1負極活物質層および第2負極活物質層から構成されたダブルレイヤー活物質層を有するものである。特に、第1負極活物質層に含まれる第1負極活物質は、SiOx(x=0)およびSiOx(0x(x=0)を95重量部以上含み、第2負極活物質層に含まれる前記第2負極活物質は、炭素系活物質、シリコン系活物質、リチウムと合金化が可能な金属系活物質およびリチウム含有窒化物からなる群から選択された1種以上を含む。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506005000001_ABST
    Figure 2025506005000001_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode for a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0136718, filed with the Korean Intellectual Property Office on October 21, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode for a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is power generation and storage using electrochemical reactions.

[0004] At present, secondary batteries are a typical example of electrochemical elements that utilize such electrochemical energy, and the range of their use is tending to expand more and more.

[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research into a method for manufacturing a high-density electrode with a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is being actively conducted.

[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.

[0007] In recent years, in response to the demand for high-density energy batteries, Si / C and SiO, which have capacities 10 times larger than those of graphite-based materials, have been used as negative electrode active materials.x Active research is being conducted into methods for increasing capacity by using silicon-based compounds such as tetrafluoroethylene (TEF) together with lithium-ion batteries. However, silicon-based compounds, which are high-capacity materials, are materials with high capacity and excellent capacity characteristics compared to conventionally used graphite, but their volume expands rapidly during charging, cutting off the conductive path and reducing battery characteristics, resulting in a drop in capacity from the beginning. In addition, when silicon-based negative electrodes are repeatedly charged and discharged, lithium ions are not uniformly charged in the depth direction of the negative electrode, and reactions proceed on the surface, accelerating surface deterioration, so performance needs to be improved in terms of battery cycles.

[0008] Therefore, in order to solve the above problems when using silicon-based compounds as negative electrode active materials, various methods are being discussed, such as a method of adjusting the driving potential, a method of coating a thin film on the active material layer, a method of controlling the particle size of the silicon-based compound, or the development of a binder that suppresses the volume expansion of the silicon-based compound to prevent the conductive path from being broken.In addition, research is being conducted to limit the usage rate of silicon-based active materials used during initial charging and discharging through a method of pre-lithiating the silicon-based active material layer, and to provide the role of a reservoir to complement the life characteristics of silicon-based negative electrodes.

[0009] However, in the case of the above method, there is a limit to its application since it may deteriorate the performance of the battery, and there is still a limit to the commercialization of negative electrode batteries having a high content of silicon-based compounds, and the higher the ratio of silicon-based active material contained in the silicon-based active material layer, the more the negative electrode surface reaction progresses, causing problems.

[0010] Therefore, even when silicon-based compounds are used as active materials, research is needed on methods that can prevent electrode surface deterioration during charge and discharge cycles and prevent the large volume expansion that results in reduced lifespan. [Prior art documents] [Patent documents]

[0011]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0012] This application relates to a method that can prevent electrode surface deterioration during charge and discharge cycles, which are existing problems, while using a silicon-based active material for the negative electrode, and can further improve the volume expansion of the silicon-based active material.

[0013] Specifically, through research, the present invention has confirmed that when the negative electrode active material layer is composed of two layers instead of a single layer to prevent the electrode surface deterioration phenomenon, and further improve the binder contained in the lower layer (the first negative electrode active material layer), the life characteristics can be improved. Accordingly, this application relates to a negative electrode for a lithium secondary battery, a method for manufacturing the negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode.

Means for Solving the Problems

[0014] One embodiment of this specification is a negative electrode for a lithium secondary battery including a negative electrode current collector layer; a first negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer provided on the opposite surface of the surface of the first negative electrode active material layer facing the negative electrode current collector layer, wherein the first negative electrode active material layer includes a first negative electrode active material layer composition containing a first negative electrode active material, the second negative electrode active material layer includes a second negative electrode active material layer composition containing a second negative electrode active material, the first negative electrode active material layer contains at least one selected from the group consisting of SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, the SiO xIt contains 95 parts by weight or more of (x = 0), the second negative electrode active material contains one or more mixtures selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, the first negative electrode active material layer composition contains a first negative electrode binder, and the first negative electrode binder contains a polymer aqueous binder including a PAM-based or PAA-based binder; and a rubber-based binder; and satisfies the following formula 1, and provides a negative electrode for a lithium secondary battery.

[0015] [Formula 1] 1 ≦ X / Y < 4 In the above formula 1, X is the part by weight of the rubber-based binder based on 100 parts by weight of the first negative electrode binder, Y is the part by weight of the aqueous binder based on 100 parts by weight of the first negative electrode binder.

[0016] Also, in one embodiment of the present application, the first negative electrode active material layer may be formed on a part or all of the surface of the negative electrode current collector layer, and the second negative electrode active material layer may be formed on a part or all of the surface of the first negative electrode active material layer.

[0017] Also, in another embodiment, a step of preparing a negative electrode current collector layer; a step of applying a first negative electrode active material layer composition containing a first negative electrode active material to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer; and a step of applying a second negative electrode active material layer composition containing a second negative electrode active material to the opposite surface of the surface of the first negative electrode active material layer facing the negative electrode current collector layer to form a second negative electrode active material layer; is a method for manufacturing a negative electrode for a lithium secondary battery, and the first negative electrode active material contains at least one selected from the group consisting of SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, the SiO x(x = 0) contains 95 parts by weight or more, the second negative electrode active material contains one or more mixtures selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, the first negative electrode active material layer composition contains a first negative electrode binder, and the first negative electrode binder contains a polymer aqueous binder including a PAM-based or PAA-based binder; and a rubber-based binder; and provides a method for manufacturing a negative electrode for a lithium secondary battery that satisfies the above formula 1.

[0018] Finally, a lithium secondary battery including a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte is provided.

Advantages of the Invention

[0019] The negative electrode for a lithium secondary battery according to an embodiment of the present invention has a double-layer active material layer composed of a first negative electrode active material layer and a second negative electrode active material layer. In particular, the first negative electrode active material contained in the first negative electrode active material layer is SiO x (x = 0) and SiO x (0 < x < 2), and contains at least one selected from the group consisting of them. Based on 100 parts by weight of the first negative electrode active material, the SiO x (x = 0) contains 95 parts by weight or more, and the second negative electrode active material contained in the second negative electrode active material layer contains one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride.

[0020] In particular, the second negative electrode active material contains at least one selected from the group consisting of a carbon-based active material, SiO x (0 < x < 2), SiC, and Si alloy, and may particularly contain SiO x (0 < x < 2).

[0021] The negative electrode for a lithium secondary battery according to the present application has a double-layer active material layer having the specific composition and content as described above. In particular, the first negative electrode active material layer is SiO xBy including a high content of (x=0), it is possible to have the advantages of high capacity, high density, and rapid charging. Furthermore, by including a silicon-based or carbon-based active material in the second negative electrode active material layer, it is possible to prevent deterioration of the electrode surface during the progress of charge and discharge cycles, and also to improve the uniformity of pre-lithiation.

[0022] In addition, the first negative electrode binder includes the above-mentioned PAM- or PAA-based polymer aqueous binder; and a rubber-based binder; and is characterized by satisfying the range of the above-mentioned formula 1. That is, the ratio of the aqueous binder for improving the dispersibility of the first negative electrode active material layer composition can be reduced, and a rubber-based binder can be further included, so that the problem of process stability in which shrinkage due to heat is deepened can be solved and the life characteristics can be enhanced. In addition, by using the first negative electrode binder with the specific composition as described above, the volume expansion can be improved and the amount of conductive material can be reduced, the thickness of the electrode can be made thinner, the capacity characteristics can be maximized, and the non-uniformity in the depth direction can be improved.

[0023] In conclusion, the negative electrode for a lithium secondary battery according to the present application is characterized in that it is configured as a double layer in which a first negative electrode active material layer and a second negative electrode active material layer are applied with specific compositions and contents in order to obtain the advantages of an electrode using a high content of Si particles as a single layer active material, while resolving the disadvantages of having such an electrode, such as surface deterioration, uniformity during pre-lithiation, and life characteristics. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 3] 1 is a flow chart illustrating a wet on dry process according to one embodiment of the present application. [Figure 4]1 is a flow chart illustrating a wet on wet process according to one embodiment of the present application. [Diagram 5] FIG. 2 is a diagram showing a method for measuring curl generation in the experimental examples of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Before describing the present invention, some terms will first be defined.

[0026] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.

[0027] In this specification, "p to q" means a range of "not less than p and not more than q".

[0028] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the above-mentioned measurement method.

[0029] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size. Meanwhile, the particle size distribution can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam is measured to calculate the particle size distribution.

[0030] In this specification, the meaning that a polymer contains a certain monomer in monomer units means that the monomer participates in a polymerization reaction and is included as a repeating unit in the polymer. In this specification, when a polymer is said to contain a monomer, this is interpreted in the same way as the polymer containing the monomer in monomer units.

[0031] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers unless otherwise specified as "homopolymer".

[0032] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are the polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight-average molecular weight unless otherwise specified.

[0033] Hereinafter, for those with ordinary knowledge in the technical field to which the present invention belongs to easily implement the present invention, a detailed description will be given with reference to the drawings. However, the present invention can be embodied in various different forms and is not limited to the following description.

[0034] One embodiment of this specification is a negative electrode for a lithium secondary battery including a negative electrode current collector layer; a first negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer provided on the opposite surface of the surface of the first negative electrode active material layer facing the negative electrode current collector layer, wherein the first negative electrode active material layer includes a first negative electrode active material layer composition containing a first negative electrode active material, the second negative electrode active material layer includes a second negative electrode active material layer composition containing a second negative electrode active material, the first negative electrode active material layer contains at least one selected from the group consisting of SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, the SiO x(x=0), the second negative electrode active material comprises a mixture of one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of being alloyed with lithium, and a lithium-containing nitride, the first negative electrode active material layer composition comprises a first negative electrode binder, the first negative electrode binder comprises a polymer aqueous binder including a PAM-based or PAA-based binder, and a rubber-based binder, and satisfies the following formula 1:

[0035] [Formula 1] 1≦X / Y<4 In the above formula 1, X is the weight part of the rubber-based binder based on 100 parts by weight of the first negative electrode binder, Y is the weight part of the aqueous binder based on 100 weight parts of the first negative electrode binder.

[0036] The negative electrode for a lithium secondary battery according to the present application has the advantage of an electrode using a high content of Si particles as a single layer active material, and is characterized in that the first negative electrode binder includes a polymer aqueous binder including the PAM or PAA system; and a rubber-based binder; and satisfies the range of the formula 1 in order to solve the problems of surface deterioration, uniformity during prelithiation, and life characteristics, which are disadvantages of the electrode having the same. That is, the proportion of the aqueous binder for improving the dispersibility of the first negative electrode active material layer composition can be reduced, and a rubber-based binder can be further included, which solves the problem of process stability in which shrinkage due to heat is deepened, and improves life characteristics. In addition, by using the first negative electrode binder having the specific composition as described above, volume expansion can be improved, the amount of conductive material can be reduced, the thickness of the electrode can be formed thinner, capacity characteristics can be maximized, and non-uniformity in the depth direction can be improved.

[0037] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a first negative electrode active material layer 20 and a second negative electrode active material layer 10 on one side of a negative electrode current collector layer 30 can be seen. Although FIG. 1 shows that the first negative electrode active material layer is formed on one side, it may be formed on both sides of the negative electrode current collector layer. As described above, in one embodiment of the present application, the first negative electrode active material layer may be formed on the entire surface of the negative electrode current collector layer, and the second negative electrode active material layer may be formed on the entire surface of the first negative electrode active material layer.

[0038] FIG. 2 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, as shown in FIG. 2, a first negative electrode active material layer 20 and a second negative electrode active material layer 10 may be formed on both sides of a negative electrode current collector layer 30. The arrangement may be 10>20>30>20>10, and further, when the first negative electrode active material layer and the second negative electrode active material layer are sequentially laminated only on one side of the negative electrode current collector layer, the arrangement on the opposite side may be any arrangement, such as 10>20>30>20, 10>20>30>10, 10>20>30>10>20, etc. It is preferable that both sides of the negative electrode current collector layer have the same composition, and specifically, the structure may be 10>20>30>20>10.

[0039] The negative electrode for a lithium secondary battery of the present invention will be described in more detail below.

[0040] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a first negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a second negative electrode active material layer provided on a side of the first negative electrode active material layer opposite to a side in contact with the negative electrode current collector layer.

[0041] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, those surface-treated with carbon, nickel, titanium, silver, etc. on the surface of copper or stainless steel, aluminum-cadmium alloy, etc. can be used. Also, fine irregularities can be formed on the surface to strengthen the binding force of the negative electrode active material, and it can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0042] In one embodiment of the present application, the thickness of the negative electrode current collector layer may be 1 μm or more and 100 μm or less.

[0043] However, the thickness can be variously deformed according to the type and use of the negative electrode used, and is not limited thereto.

[0044] In one embodiment of the present application, the first negative electrode active material contains at least one selected from the group consisting of SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, the SiO x (x = 0) may be contained in an amount of 95 parts by weight or more.

[0045] In one embodiment of the present application, the first negative electrode active material contains at least one selected from the group consisting of SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, the SiO x (x = 0) is contained in an amount of 95 parts by weight or more, preferably the SiO x (x = 0) is contained in an amount of 97 parts by weight or more, more preferably 99 parts by weight or more, and may be contained in an amount of 100 parts by weight or less.

[0046] In one embodiment of the present application, the first negative electrode active material may be, in particular, pure silicon (Si) particles. The use of pure silicon (Si) as the first negative electrode active material means that, based on a total of 100 parts by weight of the first negative electrode active material as described above, pure Si particles (SiO x (x=0)) can be included in the range.

[0047] The first negative electrode active material used in the first negative electrode active material layer of the present invention undergoes a very complicated crystal change in the reaction of electrochemically absorbing, storing, and releasing lithium atoms. As the reaction of electrochemically absorbing, storing, and releasing lithium atoms progresses, the composition and crystal structure of the silicon particles change from Si (crystal structure: Fd3m), LiSi (crystal structure: I41 / a), Li2Si (crystal structure: C2 / m), Li7Si2 (Pbam), Li 22 Si5(F23), etc. In addition, the volume of silicon particles expands by about four times due to the change in the complex crystal structure. Therefore, when the charge / discharge cycle is repeated, the silicon particles are destroyed and bonds are formed between the lithium atoms and the silicon particles, damaging the lithium atom insertion sites that the silicon particles initially had, which can significantly reduce the cycle life.

[0048] In one embodiment of the present application, the first negative electrode active material is SiO x (x=0).

[0049] The first negative electrode active material layer according to the present application contains a first negative electrode active material, specifically, SiO x The negative electrode active material layer according to the present invention includes pure silicon particles containing 95 parts by weight or more of (x=0). In this case, when the negative electrode active material layer includes a high content of pure silicon particles, the negative electrode active material layer includes the second negative electrode active material layer according to the present invention in order to solve the above problems by providing excellent capacity characteristics and solving the problems associated with the deterioration of life caused by the non-uniform surface reaction, and by improving the output characteristics and the fast charging performance.

[0050] Meanwhile, the average particle size (D50) of the first negative electrode active material of the present invention may be 3 μm to 10 μm, specifically 4 μm to 8 μm, and more specifically 5 μm to 7 μm. When the average particle size is within the above range, the specific surface area of ​​the particles is within an appropriate range, and the viscosity of the negative electrode slurry is formed within an appropriate range. This allows smooth dispersion of the particles constituting the negative electrode slurry. In addition, when the size of the first negative electrode active material is equal to or greater than the lower limit of the above range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. On the other hand, when the average particle size satisfies the above range, silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the non-uniform phenomenon of current density during charging and discharging.

[0051] In one embodiment of the present application, the first negative electrode active material generally has a characteristic BET surface area. The BET surface area of ​​the first negative electrode active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET surface area is determined according to DIN 66131 (using nitrogen).

[0052] In one embodiment of the present application, the first negative active material can be, for example, in crystalline or amorphous form, and is preferably not porous.The silicon particles are preferably spherical or shard particles.Alternatively, but less preferably, the silicon particles can also have a fibrous structure or be in the form of a silicon-containing film or coating.

[0053] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0054] In this application, the circularity is determined by the following formula 1-1, where A is the area and P is the perimeter.

[0055] [Formula 1-1] 4πA / P 2

[0056] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the first negative electrode active material is 60 parts by weight or more based on 100 parts by weight of a first negative electrode active material layer composition.

[0057] In yet another embodiment, the first negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, based on 100 parts by weight of the first negative electrode active material layer composition, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.

[0058] The first negative electrode active material layer composition according to the present application solves the problems of surface deterioration during charging and discharging, uniformity during pre-lithiation, and life characteristics without reducing the capacity performance of the entire negative electrode, even when a first negative electrode active material having an extremely high capacity is used within the above range, by using a second negative electrode active material layer described below in combination.

[0059] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but in recent years, as the demand for high-capacity batteries has increased, attempts to mix silicon-based compounds to increase capacity have been increasing. However, silicon-based compounds have a limitation in that their volume expands rapidly during the charge / discharge process, damaging the conductive path formed in the negative electrode active material layer and reducing the performance of the battery.

[0060] Therefore, in one embodiment of the present application, the first negative electrode active material layer composition may further include at least one selected from the group consisting of a first negative electrode conductive material; and a first negative electrode binder.

[0061] In this case, the first negative electrode conductive material and the first negative electrode binder contained in the first negative electrode active material layer composition may be any material commonly used in the art without any limitations.

[0062] In one embodiment of the present application, the first negative electrode conductive material may be any material that can be commonly used in the art without limitation, and may specifically include at least one selected from the group consisting of dot-shaped conductive materials; planar conductive materials; and linear conductive materials.

[0063] The details regarding the first negative electrode conductive material are similar to those regarding the second negative electrode conductive material described below, and will be described later.

[0064] In one embodiment of the present application, the first negative electrode binder includes a polymer aqueous binder including a PAM system or a PAA system; and a rubber-based binder; and provides a negative electrode for a lithium secondary battery that satisfies the following formula 1:

[0065] [Formula 1] 1≦X / Y<4 In the above formula 1, X is the weight part of the rubber-based binder based on 100 parts by weight of the first negative electrode binder, Y is the weight part of the aqueous binder based on 100 weight parts of the first negative electrode binder.

[0066] Generally, one-part aqueous binders have been used as binders for silicon-based negative electrodes. In other words, aqueous binders that have low adhesive strength but can improve dispersibility have been used to disperse silicon-based active materials that have hard properties. However, because aqueous binders also have high rigidity, problems such as curling due to the action of stress during drying have occurred.

[0067] Therefore, it has been found that when a specific binder satisfying the above composition and content is used as the first negative electrode binder according to the present application, the dispersibility can be improved and the adhesive strength can be satisfied, thereby enhancing the life characteristics of the negative electrode for a lithium secondary battery.

[0068] In one embodiment of the present application, the first negative electrode binder may include a polymeric aqueous binder, and the polymeric aqueous binder has a Young's modulus of 1×10 3 MPa or more.

[0069] In another embodiment, the polymeric aqueous binder has a Young's modulus of 1×10 3 MPa or more, preferably 2×10 3 MPa, more preferably 5×10 3 MPa or more, and 20×10 3 MPa or less, preferably 18×10 3 MPa or less, more preferably 15×10 3 MPa or less.

[0070] The polymer aqueous binder has dispersibility for dispersing the negative electrode active material in a negative electrode slurry state containing the negative electrode composition, and adhesive strength for binding the negative electrode current collector layer and the negative electrode active material layer after drying, and corresponds to a binder whose adhesive strength is not very high. That is, the polymer aqueous binder according to the present application may mean a binder that satisfies the Young's modulus and has a surface-adhesive form.

[0071] In one embodiment of the present application, the polymeric aqueous binder is dissolved in an aqueous solvent such as water, and includes at least one selected from the group consisting of polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG), polyacrylonitrile (PAN) and polyacrylamide (PAM). Preferably, the polymeric aqueous binder includes at least one selected from the group consisting of polyacrylic acid (PAA) and polyacrylamide (PAM), more preferably polyacrylic acid (PAA) and polyacrylamide (PAM), in terms of excellent resistance to volume expansion / contraction of silicon-based active materials.

[0072] More specifically, the polymer aqueous binder may be a PAM-based binder. In this case, the PAM-based binder is a binder mainly composed of PAM, and the ratio of PAM, PAA, and PAN may be adjusted for use. The composition may be appropriately changed to satisfy the Young's modulus.

[0073] The polymer aqueous binder may include a polymer aqueous binder in which hydrogen is substituted with Li, Na, Ca, or the like in order to better disperse in an aqueous solvent such as water when preparing a negative electrode slurry for forming a negative electrode active material layer and to more smoothly coat the active material to improve binding strength.

[0074] The polymer aqueous binder is hydrophilic and does not dissolve in electrolytes or electrolyte solutions generally used in secondary batteries. This characteristic can impart strong stress or tensile strength to the polymer aqueous binder when applied to anodes or lithium secondary batteries, thereby effectively suppressing the volume expansion / contraction problem associated with charge / discharge of silicon-based active materials.

[0075] In one embodiment of the present application, the weight average molecular weight of the polymeric aqueous binder may be 100,000 g / mol or more and 1,000,000 g / mol or less.

[0076] In one embodiment of the present application, the rubber-based binder may have a strain of 15% or more, preferably a strain of 20% or more, more preferably a strain of 30% or more, and most preferably a strain of 40% or more, and a strain of 80% or less, preferably 70% or less, and more preferably 60% or less.

[0077] In this case, the strain value of the rubber binder can be realized within the above-mentioned range by adjusting the ST / BD ratio of the SBR binder within an appropriate range.

[0078] In one embodiment of the present application, the rubber-based binder is a substance different from the polymer aqueous binder, and can be defined as a substance that is not very soluble in an aqueous solvent such as water, but can be smoothly dispersed in an aqueous solvent.

[0079] Specifically, the rubber-based binder having a strain of 15% or more may include at least one selected from the group consisting of styrene butadiene rubber (SBR), hydrogenated nitrile butadiene rubber (HNBR), acrylonitrile butadiene rubber, acrylic rubber, butyl rubber, and fluoro rubber, and preferably includes at least one selected from the group consisting of styrene butadiene rubber and hydrogenated nitrile butadiene rubber, more preferably styrene butadiene rubber, in terms of ease of dispersion and excellent phase stability.

[0080] In general, rubber-based binders are materials that have a very high wettability with electrolytes compared to polymeric water-based binders. When the aforementioned rubber-based binder is located near the surface of the silicon-based anode, the FEC solvent and LiPF6 salt that can create the SEI layer can be rapidly supplied, resulting in low anode resistance.

[0081] In one embodiment of the present application, the formula 1 may satisfy 1≦X / Y<4, preferably 1.1≦X / Y<3.9, and more preferably 1.2≦X / Y<3.8.

[0082] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein X is 50 parts by weight or more and 95 parts by weight or less, and Y is 5 parts by weight or more and 50 parts by weight or less.

[0083] In another embodiment, the X may be 50 parts by weight or more and 95 parts by weight or less, preferably 55 parts by weight or more and 90 parts by weight or less, and more preferably 55 parts by weight or more and 80 parts by weight or less, based on 100 parts by weight of the first negative electrode binder.

[0084] In another embodiment, the Y may be 5 parts by weight or more and 50 parts by weight or less, preferably 10 parts by weight or more and 45 parts by weight or less, and more preferably 20 parts by weight or more and 45 parts by weight or less, based on 100 parts by weight of the first negative electrode binder.

[0085] As described above, the first negative electrode binder according to the present application satisfies the above-mentioned contents of the polymer aqueous binder and the rubber-based binder, and has the characteristics of improving dispersibility and solving the problem of adhesive strength even when a silicon-based active material is used.

[0086] That is, when the polymer aqueous binder is used alone, there is a risk of the negative electrode warping, the occurrence of cracks due to the warping, and a decrease in life characteristics. Therefore, by including the rubber-based binder within the range of formula 1, the rubber-based binder is well dissolved in the electrolyte or electrolytic solution generally used in secondary batteries, and when used in combination with the polymer aqueous binder, the stress of the polymer aqueous binder can be reduced to a certain level.

[0087] Therefore, the first negative electrode binder of the present invention has the characteristics that, by satisfying the specific weight ratio (within the range of formula 1) of the aqueous binder and the rubber-based binder, the volume expansion / contraction problem of the silicon-based active material can be effectively solved, thereby improving the life characteristics, the warping problem during the manufacture of the thin film negative electrode can be solved, and the adhesive strength can also be improved.

[0088] Furthermore, by including the first negative electrode binder, the amount of conductive material can be reduced due to improved volume expansion, and thus the thickness of the electrode can be made thinner, thereby maximizing capacitance characteristics and improving non-uniformity in the depth direction.

[0089] In one embodiment of the present application, the first negative electrode binder is 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the first negative electrode active material layer composition, and may be 5 parts by weight or more, or 10 parts by weight or more.

[0090] In one embodiment of the present application, the second negative electrode active material may include a mixture of one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of being alloyed with lithium, and a lithium-containing nitride.

[0091] In this case, the silicon-based active material is contained in an amount of 60 parts by weight or more based on 100 parts by weight of the second negative electrode active material.

[0092] In another embodiment, based on 100 parts by weight of the second negative electrode active material, the silicon-based active material may be contained in an amount of 60 parts by weight or more, preferably 70 parts by weight or more, more preferably 80 parts by weight or more, and may be contained in an amount of 100 parts by weight or less. The second negative electrode active material may be composed of a silicon-based active material.

[0093] In the second negative electrode active material layer, when the parts by weight of the silicon-based active material are less than the above range, during the progress of charge and discharge cycles, rather, the second negative electrode active material layer acts as a resistance layer and the capacity retention rate decreases, thereby causing a problem that the resistance increase rate of the negative electrode becomes high.

[0094] In one embodiment of the present application, the silicon-based active material contained in the second negative electrode active material is SiO x (0 < x < 2), SiC, and at least one selected from the group consisting of Si alloys may be included.

[0095] In one embodiment of the present application, the silicon-based active material is SiO x (0 < x < 2); or a negative electrode for a lithium secondary battery containing SiC is provided.

[0096] In another embodiment, the silicon-based active material contained in the second negative electrode active material may contain SiO x (0 < x < 2).

[0097] In another embodiment, the silicon-based active material contained in the second negative electrode active material may contain SiC.

[0098] In another embodiment, the second negative electrode active material is a silicon-based active material, and the silicon-based active material is SiO x (0 < x < 2).

[0099] The negative electrode for a lithium secondary battery according to the present application is configured with a double layer, and as described above, the second negative electrode active material layer contains the second negative electrode active material. Since the negative electrode contains the first negative electrode active material described above, it maintains high capacity and high density characteristics, while resolving the problems of surface deterioration during charge and discharge, uniformity during pre-lithiation, and life characteristics.

[0100] In one embodiment of the present application, the carbon-based active material may be, for example, natural graphite, artificial graphite, expanded graphite, carbon fiber, non-graphitizable carbon, carbon black, carbon nanotubes, fullerene, or activated carbon. Any carbon-based active material that is commonly used in carbon materials for lithium secondary batteries may be used without limitation. Specifically, the carbon-based active material may be processed into a spherical or dot-like shape and used.

[0101] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the carbon-based active material comprises graphite, the graphite comprises artificial graphite and natural graphite, and a weight ratio of the artificial graphite to the natural graphite is 5:5 to 9.5:0.5.

[0102] The artificial graphite according to an embodiment of the present invention may be in the form of primary particles, or in the form of secondary particles formed by agglomeration of a plurality of the primary particles.

[0103] The term "primary particle" as used herein means the original particle from which other types of particles are formed, and multiple primary particles can aggregate, combine or assemble to form secondary particles.

[0104] As used herein, the term "secondary particles" refers to larger physically distinct particles formed by the aggregation, bonding, or assembly of individual primary particles.

[0105] The primary particle artificial graphite may be produced by heat treating one or more selected from the group consisting of needle cokes, mosaic cokes, and coal tar pitch.

[0106] The artificial graphite is generally produced by carbonizing raw materials such as coal tar, coal tar pitch, and heavy petroleum oil at 2,500°C or higher, and can be used as an anode active material after such graphitization and adjusting the particle size by crushing and forming secondary particles. In the case of artificial graphite, crystals are randomly distributed within the particles, and compared to natural graphite, it has a lower degree of sphericity and a slightly pointed shape.

[0107] The artificial graphite used in an embodiment of the present invention may be MCMB (mesophase carbon microbeads), MPCF (mesophase pitch-based carbon fiber), artificial graphite graphitized in a block form, artificial graphite graphitized in a powder form, etc. The sphericity of the artificial graphite may be 0.91 or less, or 0.6 to 0.91, or 0.7 to 0.9.

[0108] The artificial graphite may have a particle size of 5 μm to 30 μm, and preferably 10 μm to 25 μm.

[0109] Specifically, the D50 of the primary particles of the artificial graphite may be 6 μm to 15 μm, 6 μm to 10 μm, or 6 μm to 9 μm. When the D50 of the primary particles satisfies this range, the primary particles can be formed to a degree that has high graphitization, the orientation index of the negative electrode active material particles can be appropriately ensured, and the fast charging performance can be improved.

[0110] The artificial graphite secondary particles may be formed by assembling primary particles. That is, the secondary particles may be structures formed by agglomerating the primary particles to each other through an assembling process. The secondary particles may include a carbonaceous matrix that aggregates the primary particles. The carbonaceous matrix may include at least one of soft carbon and graphite. The soft carbon may be formed by heat treating pitch.

[0111] The carbonaceous matrix may be contained in the secondary particles in an amount of 8% by weight to 16% by weight, specifically 9% by weight to 12% by weight. This range is a lower level than the carbonaceous matrix content used in typical artificial graphite secondary particles. This is because the particle size of the primary particles in the secondary particles is controlled, and structurally stable secondary particles can be produced even if the content of the carbonaceous matrix required for assembly is small, and the amount of primary particles constituting the secondary particles can be uniform.

[0112] The artificial graphite secondary particles may include a carbon coating layer on a surface thereof, the carbon coating layer including at least one of amorphous carbon and crystalline carbon.

[0113] The crystalline carbon may further improve the electrical conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene and graphene.

[0114] The amorphous carbon can appropriately maintain the strength of the coating layer and suppress the expansion of the natural graphite. The amorphous carbon may be a carbon-based material formed by using at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a hydrocarbon as a source for a chemical vapor deposition process.

[0115] The carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or kedohexose, and combinations thereof.

[0116] The D50 of the secondary particles of artificial graphite may be 10 μm to 25 μm, specifically 12 μm to 22 μm, and more specifically 13 μm to 20 μm. When the above range is satisfied, the secondary particles of artificial graphite may be uniformly dispersed in the slurry, and the charging performance of the battery may be improved.

[0117] The tap density of the artificial graphite secondary particles may be 0.85 g / cc to 1.30 g / cc, specifically 0.90 g / cc to 1.10 g / cc, and more specifically 0.90 g / cc to 1.07 g / cc. When the tap density satisfies the above range, the packing of the artificial graphite secondary particles in the negative electrode is smoothly performed, which means that the adhesive strength of the negative electrode can be improved.

[0118] The natural graphite may generally be in the form of plate-like agglomerates before being processed, and the plate-like particles may be produced in the form of spheres having smooth surfaces by post-processing such as particle crushing and reassembly to be used as an active material for electrode manufacture.

[0119] The natural graphite used in one embodiment of the present invention may have a sphericity of more than 0.91 and less than or equal to 0.97, or from 0.93 to 0.97, or from 0.94 to 0.96.

[0120] The natural graphite may have a particle size of 5 μm to 30 μm, or 10 μm to 25 μm.

[0121] According to an embodiment of the present invention, the weight ratio of the artificial graphite to the natural graphite may be 5:5 to 9.5:0.5, or 5:5 to 9.3:0.7, or 5:5 to 9:1, or 6:4 to 9:1. When the weight ratio of the artificial graphite to the natural graphite satisfies such a range, a better output may be exhibited, which may be advantageous in terms of life span and quick charging performance.

[0122] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and a role different from those of the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and means a material that is processed into a spherical or dotted shape to facilitate the storage and release of lithium ions.

[0123] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and can be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play a role in storing and releasing lithium, but means a material for securing a planar conductive path inside the negative electrode active material layer.

[0124] That is, in the present application, the use of plate-like graphite as a conductive material means that it is used as a material that ensures a conductive path, rather than being processed into a planar or plate-like shape to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.

[0125] Meanwhile, in the present application, the use of a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and is used as a material that serves to store or release lithium.

[0126] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, has a BET specific surface area of ​​0.1 m2 4.5 m or more per g 2 It may satisfy the range of 4.5 m or less per g. Further, the plate-shaped graphite which is a planar conductive material may have a planar BET specific surface area of 5 m 2 or more per g.

[0127] The metal-based active material may be, as a representative example thereof, a compound containing any one or two or more metal elements selected from the group consisting of Al, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti, Sb, Ga, Mn, Fe, Co, Ni, Cu, Sr, Ba, etc. These metal compounds may be used in any form such as a single substance, an alloy, an oxide (such as TiO2, SnO2), a nitride, a sulfide, a boride, an alloy with lithium, etc., but a single substance, an alloy, an oxide, and an alloy with lithium can achieve a higher capacity.

[0128] As described above, when the second negative electrode active material satisfies the above composition and content, a lithium secondary battery with improved various performances such as cycle life characteristics can be manufactured. That is, in the present application, the second negative electrode active material layer serves as a buffer layer. In order to solve the problems of surface deterioration during charge and discharge, the uniformity problem during pre-lithiation, and the life characteristic problem, the SiO x (0 < x < 2) and / or by including a carbon-based active material, the intense reaction with lithium ions on the surface of the second negative electrode active material layer can be suppressed.

[0129] Ultimately, the second negative electrode active material layer according to the present application has the above composition and content, solves the problem of surface deterioration during charge and discharge cycle continuation, and can have the effect of pre-lithiation even if pre-lithiation does not occur up to the first negative electrode active material layer during pre-lithiation, and has the characteristic of being able to provide a negative electrode for a high-capacity and high-density lithium secondary battery.

[0130] In one embodiment of the present application, the second negative electrode active material provides a negative electrode for a lithium secondary battery that is 60 parts by weight or more based on 100 parts by weight of the second negative electrode active material layer composition.

[0131] In another embodiment, the second negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less, based on 100 parts by weight of the second negative electrode active material layer composition, and most preferably 75 parts by weight or more and 80 parts by weight or less.

[0132] The second negative electrode active material layer composition according to the present application has a feature of enhancing life characteristics without deteriorating the capacity performance of the negative electrode by using the second negative electrode active material in the above range, which has lower capacity characteristics than the first negative electrode active material but is less susceptible to particle cracking during the progress of charge / discharge cycles or pre-lithiation. In addition, when the composition contains a content of the second negative electrode active material as described above, the output characteristics can be enhanced, thereby improving the fast charging performance.

[0133] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the second negative electrode active material layer comprises a second negative electrode active material layer composition including: a second negative electrode active material; a second negative electrode conductive material; and a second negative electrode binder.

[0134] In this case, the second negative electrode conductive material may include at least one selected from the group consisting of a dot-like conductive material, a linear conductive material, and a sheet-like conductive material.

[0135] In one embodiment of the present application, the dot-like conductive material refers to a dot-like or spherical conductive material that can be used to improve the conductivity to the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-like conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably include carbon black in that it realizes high conductivity and has excellent dispersibility.

[0136] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of ​​40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.

[0137] In one embodiment of the present application, the particle diameter of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0138] In one embodiment of the present application, the second negative electrode conductive material may include a sheet conductive material.

[0139] The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode, and at the same time, can suppress the disconnection of the conductive path due to volume expansion, and can be expressed as a plate-shaped conductive material or a bulk-type conductive material.

[0140] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may be preferably platelet graphite.

[0141] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the range is satisfied, the sufficient particle size makes it easy to disperse without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersing using the same equipment and time, the dispersion effect is excellent.

[0142] In one embodiment of the present application, the sheet conductive material provides a negative electrode composition having a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.

[0143] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.

[0144] In one embodiment of the present application, the sheet conductive material may be a high-specific surface area sheet conductive material or a low-specific surface area sheet conductive material without any restrictions. However, the sheet conductive material in the present application may be affected to some extent by dispersion in terms of electrode performance, and it may be particularly preferable to use a low-specific surface area sheet conductive material that does not cause dispersion problems.

[0145] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of ​​5 m 2 / g or more.

[0146] In another embodiment, the sheet conductive material has a BET specific surface area of ​​5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g or less.

[0147] In another embodiment, the sheet conductive material is a high specific surface area sheet conductive material having a BET specific surface area of ​​50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.

[0148] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of ​​5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.

[0149] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are arranged in a substantially uniform orientation with their longitudinal axes or are entangled. The carbon nanotube units have a graphite sheet with a nano-sized diameter and a cylindrical shape with an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure at which it is wound. The bundled carbon nanotubes may be more uniformly dispersed during the manufacture of the negative electrode than entangled carbon nanotubes, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0150] In particular, the linear conductive material according to one embodiment of the present application may be a single-walled carbon nanotube (SWCNT).

[0151] The single-walled carbon nanotube is a material in which carbon atoms arranged in a hexagonal shape form a tube, and can exhibit insulator, conductor or semiconductor properties depending on its unique chirality. The carbon atoms are linked by strong covalent bonds, and the tensile strength is about 100 times greater than that of steel, and the material has excellent flexibility and elasticity, as well as being chemically stable.

[0152] The average diameter of the single-walled carbon nanotubes is 0.5 nm to 15 nm. According to an embodiment of the present invention, the average diameter of the single-walled carbon nanotubes may be 1 nm to 10 nm, or 1 nm to 5 nm, or 1 nm to 2 nm. When the average diameter of the single-walled carbon nanotubes satisfies such a range, the electrical conductivity of the negative electrode can be maintained even if the single-walled carbon nanotubes are contained in a very small content, and a preferable viscosity and solid content can be obtained during the preparation of the conductive material dispersion. In the conductive material dispersion, the single-walled carbon nanotubes may be present in an entangled state (aggregate) in which they are entangled with each other. Therefore, the average diameter can be calculated by confirming the diameter of any entangled single-walled carbon nanotube aggregate extracted from the conductive material dispersion by SEM or TEM, and then dividing the diameter of the aggregate by the number of single-walled carbon nanotubes constituting the aggregate.

[0153] The BET specific surface area of ​​the single-walled carbon nanotubes is 500 m 2 / g~1,500m 2 / g, or 900m 2 / g~1,200m 2 / g, specifically 250m 2 / g~330m 2 / g. When the above range is satisfied, a conductive material dispersion having a preferable solid content is obtained, and the viscosity of the negative electrode slurry is prevented from excessively increasing. The BET specific surface area can be measured by a nitrogen adsorption BET method.

[0154] The aspect ratio of the single-walled carbon nanotube may be 50 to 20,000, or the length of the single-walled carbon nanotube may be 5 μm to 100 μm, or 5 μm to 50 μm. When the aspect ratio or length satisfies such a range, the specific surface area is high, so that the single-walled carbon nanotube can be strongly attracted to the active material particles in the negative electrode. As a result, the conductive network can be smoothly maintained even during the volume expansion of the negative electrode active material. The aspect ratio can be determined by averaging the aspect ratios of 15 single-walled carbon nanotubes with a large aspect ratio and 15 single-walled carbon nanotubes with a small aspect ratio when observing the single-walled carbon nanotube powder through a SEM.

[0155] The single-walled carbon nanotube has a larger aspect ratio, a longer length, and a larger volume than multi-walled or double-walled carbon nanotubes, and is therefore advantageous in that an electrical network can be constructed even when only a small amount is used.

[0156] In one embodiment of the present application, the second negative electrode conductive material may be 1 part by weight or more and 40 parts by weight or less based on 100 parts by weight of the second negative electrode active material layer composition.

[0157] In yet another embodiment, the second negative electrode conductive material may be 1 part by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 15 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the second negative electrode active material layer composition.

[0158] In one embodiment of the present application, the second negative electrode conductive material includes dot-like conductive material; sheet-like conductive material; and linear conductive material, and the dot-like conductive material:sheet-like conductive material:linear conductive material may satisfy a ratio of 1:1:0.01 to 1:1:1.

[0159] In one embodiment of the present application, the dot-shaped conductive material may satisfy the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the second negative electrode conductive material.

[0160] In one embodiment of the present application, the sheet conductive material may satisfy the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the second negative electrode conductive material.

[0161] In one embodiment of the present application, the linear conductive material may satisfy the range of 0.01 parts by weight or more and 10 parts by weight or less, preferably 0.05 parts by weight or more and 8 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the second negative electrode conductive material.

[0162] In one embodiment of the present application, the second negative electrode conductive material may include a linear conductive material; and a planar conductive material.

[0163] In one embodiment of the present application, the second negative electrode conductive material may include a linear conductive material and a sheet conductive material, and a ratio of the linear conductive material:sheet conductive material may satisfy 0.01:1 to 0.1:1.

[0164] In one embodiment of the present application, the second negative electrode conductive material particularly includes a linear conductive material and a planar conductive material, and by satisfying the above-mentioned compositions and ratios, the battery does not have a significant effect on the life characteristics of existing lithium secondary batteries, and the number of points at which charging and discharging are possible increases, resulting in excellent output characteristics at a high C-rate.

[0165] The first negative electrode conductive material according to the present application provides a negative electrode for a lithium secondary battery, which includes at least a linear conductive material.

[0166] The second negative electrode conductive material according to the present application provides a negative electrode for a lithium secondary battery, which includes at least a linear conductive material.

[0167] In one embodiment of the present application, the second negative electrode conductive material may be made of a linear conductive material.

[0168] The second negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the second negative electrode conductive material according to the present application serves to capture the contact between the silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, and the positive electrode conductive material serves to provide some conductivity while acting as a buffer when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.

[0169] In addition, the second negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a conductive material applied together with a silicon-based active material as in the present invention.

[0170] In this case, the first negative electrode conductive material may be the same as the second negative electrode conductive material.

[0171] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the first negative electrode active material layer has a thickness of 10 μm or more and 200 μm or less, and the second negative electrode active material layer has a thickness of 10 μm or more and 100 μm or less. The first negative electrode active material layer and the second negative electrode active material layer may be formed on both sides of a negative electrode current collector layer, and may have the same thickness as described above.

[0172] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the loading amount (a) of the first negative electrode active material layer composition is at least twice the loading amount (b) of the second negative electrode active material layer composition.

[0173] In another embodiment, the loading amount (a) of the first negative electrode active material layer composition may be in the range of 1.5 to 10 times, preferably 2.2 to 6 times, the loading amount (b) of the second negative electrode active material layer composition.

[0174] The loading amount may refer to the weight of a composition for forming a negative electrode active material layer, and specifically, the loading amount of the composition may have the same meaning as the loading amount of a slurry including the composition.

[0175] In one embodiment of the present application, the loading amount (a) of the first negative electrode active material layer composition is 2 mg / cm 2 More than 5mg / cm 2 Less than 2.2 mg / cm, preferably 2.2 mg / cm 2 More than 4mg / cm 2 The following ranges may be satisfied:

[0176] In one embodiment of the present application, the loading amount (b) of the second negative electrode active material layer composition is 0.5 mg / cm 2 More than 1.5mg / cm 2 Less than 0.8 mg / cm, preferably 0.8 mg / cm 2 More than 1.3mg / cm 2 The following ranges may be satisfied:

[0177] The first negative electrode active material layer composition and the second negative electrode active material layer composition have the loading amounts, so that the ratio of the active materials contained in the first negative electrode active material layer and the second negative electrode active material layer can be adjusted. That is, the amount of the first negative electrode active material contained in the first negative electrode active material layer can be adjusted to optimize the capacity characteristics, and the amount of the second negative electrode active material contained in the second negative electrode active material layer can be adjusted to suppress the surface reaction of the negative electrode without deteriorating the capacity characteristics, thereby improving the life characteristics.

[0178] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be a pre-lithiated negative electrode.

[0179] In one embodiment of the present application, the first negative electrode active material layer may be formed on the entire surface of the negative electrode current collector layer, and the second negative electrode active material layer may be formed on the entire surface of the first negative electrode active material layer.

[0180] In one embodiment of the present application, a step of preparing a negative electrode current collector layer; a step of applying a first negative electrode active material layer composition containing a first negative electrode active material to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer; and a step of applying a second negative electrode active material layer composition containing a second negative electrode active material to the opposite surface of the surface of the first negative electrode active material layer facing the negative electrode current collector layer to form a second negative electrode active material layer; A method for manufacturing a negative electrode for a lithium secondary battery, wherein the first negative electrode active material includes at least one selected from the group consisting of SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, the SiO x (x = 0) contains 95 parts by weight or more, and the second negative electrode active material includes one or more mixtures selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride. The first negative electrode active material layer composition includes a first negative electrode binder, and the first negative electrode binder includes a polymer aqueous binder including a PAM-based or PAA-based binder; and a rubber-based binder; A method for manufacturing a negative electrode for a lithium secondary battery that satisfies the above formula 1 is provided.

[0181] In the method for manufacturing the negative electrode, the composition and content included in each step can be applied to the above-mentioned content.

[0182] In one embodiment of the present application, a step of applying a first negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer is provided.

[0183] That is, the step is a step of forming an active material layer on a negative electrode current collector layer, and may refer to a step of forming an active material layer on a surface (lower layer) in contact with the current collector layer in a double layer structure. In addition, when the first negative electrode active material layer is formed on both sides of the negative electrode current collector layer, the second negative electrode active material layer may be applied to one or both sides of the first negative electrode active material layer.

[0184] In one embodiment of the present application, applying the first negative electrode active material layer composition includes applying and drying a first negative electrode slurry including the first negative electrode active material layer composition; and a negative electrode slurry solvent.

[0185] In this case, the solid content of the first negative electrode slurry may be in the range of 10% to 40%.

[0186] In one embodiment of the present application, forming the first negative electrode active material layer may include mixing the first negative electrode slurry; and coating the mixed first negative electrode slurry on one or both sides of the negative electrode current collector layer, and the coating may be performed using a coating method commonly used in the art.

[0187] In one embodiment of the present application, a step of forming a second negative electrode active material by coating a second negative electrode active material layer composition on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer is provided.

[0188] That is, the step refers to a step of forming a second negative electrode active material layer on the first negative electrode active material layer, and may refer to a step of forming an active material layer on a surface (upper layer) away from the current collector layer in a double layer structure.

[0189] In one embodiment of the present application, applying the second negative electrode active material layer composition includes applying and drying a second negative electrode slurry including the second negative electrode active material layer composition; and a negative electrode slurry solvent.

[0190] In this case, the solid content of the second negative electrode slurry may be in the range of 10% to 40%.

[0191] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the forming of the second negative electrode active material layer includes: mixing the second negative electrode slurry; and coating the mixed second negative electrode slurry on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer.

[0192] The coating may be performed using any coating method commonly used in the art.

[0193] The description of the forming of the first negative electrode active material layer may be similarly applied to the forming of the second negative electrode active material layer.

[0194] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet on dry process or a wet on wet process.

[0195] In one embodiment of the present application, the wet-on-dry process may refer to a process of applying a first negative electrode active material layer composition, partially or completely drying it, and applying a second negative electrode active material layer composition thereon.

[0196] 3 is a flow chart showing a wet on dry process according to an embodiment of the present application. Specifically, in the wet on dry process, a first negative electrode slurry mixture (first negative electrode active material, first negative electrode conductive material, first negative electrode binder, first solvent) is prepared and applied to a negative electrode current collector layer. Then, the first negative electrode slurry mixture is dried to form a first negative electrode active material layer. Then, a second negative electrode slurry mixture is prepared and applied to the first negative electrode active material layer, and dried to form a second negative electrode active material layer. Then, each layer is rolled and pressed to form a negative electrode for a lithium secondary battery according to the present application.

[0197] In one embodiment of the present application, the wet-on-wet process refers to a process of applying a first negative electrode active material layer composition thereon, without drying, and then applying a second negative electrode active material layer composition thereon.

[0198] 4 is a flow chart showing a wet on wet process according to one embodiment of the present application. Specifically, in the wet on wet process, a first negative electrode slurry mixture is prepared and applied to a negative electrode current collector layer, and at the same time, a second negative electrode slurry mixture is prepared and applied to the first negative electrode slurry mixture, and the first and second negative electrode slurry mixtures are dried. Then, each layer is rolled and pressed to form a negative electrode for a lithium secondary battery according to the present application.

[0199] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet on dry process, the wet on dry process including the steps of: applying a first negative electrode active material layer composition; partially or fully drying the applied first negative electrode active material layer composition to form a first negative electrode active material layer; and applying the second negative electrode active material layer composition on the first negative electrode active material layer.

[0200] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet-on-wet process, the wet-on-wet process including: applying a first negative electrode active material layer composition; and applying the second negative electrode active material layer composition to the first negative electrode active material layer composition while the first negative electrode active material layer composition is still wet.

[0201] In particular, the wet on dry process involves coating a first negative electrode active material layer composition, partially or completely drying it, and then coating a second negative electrode active material layer composition on top of it, and through the above process, the first negative electrode active material layer and the second negative electrode active material layer can have a clear boundary. As a result, the compositions contained in the first negative electrode active material layer and the second negative electrode active material layer do not mix, resulting in a double layer configuration.

[0202] In one embodiment of the present application, the negative electrode slurry solvent may be used without limitation as long as it can dissolve the first negative electrode active material layer composition and the second negative electrode active material layer composition, and specifically, water or NMP may be used.

[0203] As a result of the wet-on-wet process, a junction region where the first and second negative electrode active material layers are mixed may be formed. In this case, for the wet-on-wet process to occur, intermixing of the first and second negative electrode active material layers may occur in the junction region and process only when the viscosity of the first negative electrode active material layer composition is lower than the viscosity of the second negative electrode active material layer composition.

[0204] The negative electrode for the lithium secondary battery described above has a first negative electrode active material layer formed of SiO x (x=0), and the second negative electrode active material layer contains the specific composition of the silicon-based active material and / or carbon-based active material described above, so that the advantage of fast charging can be retained. Furthermore, since the second negative electrode active material has the above composition and is highly irreversible, a particularly advantageous effect is obtained during the pre-lithiation process in which the negative electrode is pre-filled. Compared to the case where only the first negative electrode active material layer is simply applied, the second negative electrode active material has the second negative electrode active material having the above composition, so that a uniform pre-lithiation process can be performed on the upper end of the negative electrode, which results in a further improved lifespan.

[0205] In one embodiment of the present application, the porosity of the first and second negative electrode active material layers may be in the range of 10% or more and 60% or less.

[0206] In still another embodiment, the porosity of the first and second negative electrode active material layers may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0207] The porosity varies depending on the composition and content of the active material, conductive material, and binder contained in the first and second negative electrode active material layers, and is characterized by the fact that the electrode has an appropriate range of electrical conductivity and resistance.

[0208] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

[0209] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0210] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0211] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0212] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.6); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.

[0213] In one embodiment of the present application, the positive electrode active material includes a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), and the lithium transition metal composite compound includes single particles or secondary particles, and the average particle size (D50) of the single particles may be 1 μm or more.

[0214] For example, the average particle size (D50) of the single particles may be 1 μm or more and 12 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 6 μm or less, more than 1 μm and 12 μm or less, more than 1 μm and 8 μm or less, or more than 1 μm and 6 μm or less.

[0215] The single particle can have excellent particle strength even if it is formed with a small particle size having an average particle size (D50) of 1 μm or more and 12 μm or less. For example, the single particle can have a strength of 650 kgf / cm 2 When the particle is rolled with a force of 650 kgf / cm, the particle strength is 100 MPa to 300 MPa. 2 Even if the electrode is rolled with a strong force, the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, thereby improving the life characteristics of the battery.

[0216] The single particles may be prepared by mixing a transition metal precursor and a lithium source material and sintering the mixture. The secondary particles may be prepared by a method different from that of the single particles, and the composition of the secondary particles may be the same as or different from that of the single particles.

[0217] The method for forming the single particles is not particularly limited, but generally, the single particles can be formed by over-firing at an elevated firing temperature, and can be prepared by using additives such as grain growth promoters that are useful for over-firing, or by changing the starting material.

[0218] For example, the sintering is performed at a temperature at which single particles can be formed. To form the single particles, the sintering should be performed at a higher temperature than that at which the secondary particles are produced. For example, when the precursor composition is the same, the sintering should be performed at a temperature about 30°C to 100°C higher than that at which the secondary particles are produced. The sintering temperature for forming the single particles may vary depending on the metal composition in the precursor. For example, when a high-content nickel (High-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol% or more is to be formed into single particles, the sintering temperature may be about 700°C to 1000°C, preferably about 800°C to 950°C. When the sintering temperature satisfies the above range, a positive electrode active material including single particles having excellent electrochemical properties can be produced. When the sintering temperature is less than 790°C, a positive electrode active material including a lithium transition metal composite compound in the form of secondary particles can be produced, and when the sintering temperature exceeds 950°C, the sintering occurs excessively, the layered crystal structure is not formed well, and the electrochemical properties may be deteriorated.

[0219] In this specification, the term "single particle" is used to distinguish it from conventional secondary particles formed by agglomeration of tens to hundreds of primary particles, and is a concept that includes a single particle consisting of one primary particle and a pseudo-single particle that is an agglomeration of 30 or less primary particles.

[0220] Specifically, in the present invention, a single particle may be a single particle consisting of one primary particle or a quasi-single particle that is an aggregate of 30 or less primary particles, and a secondary particle may be in the form of an aggregate of several hundred primary particles.

[0221] In one embodiment of the present application, the lithium transition metal composite compound serving as the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.

[0222] In the present invention, the single particle may be a single particle consisting of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.

[0223] The lithium transition metal composite compound may further include secondary particles. The secondary particles refer to a form formed by agglomeration of primary particles, and can be distinguished from the concept of a single particle including one primary particle, one single particle, or a pseudo-single particle which is an agglomeration of 30 or less primary particles.

[0224] The particle diameter (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles is less than 0.05 m 2 / g~10m 2 / g, preferably 0.1m 2 / g~1m 2 / g, and more preferably 0.3m 2 / g~0.8m 2 / g.

[0225] In a further embodiment of the present application, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size (D50) of 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of aggregates of several hundred primary particles, and the primary particles may have an average particle size (D50) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.

[0226] When the average particle size (D50) of the primary particles is within the above range, a single particle positive electrode active material having excellent electrochemical properties can be formed. If the average particle size (D50) of the primary particles is too small, the number of agglomerates of the primary particles forming the lithium nickel oxide particles increases, and the effect of suppressing particle cracking during rolling decreases. If the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes long, increasing resistance and causing a decrease in output characteristics.

[0227] According to a further embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, so that the single particles can have excellent particle strength even if they are formed with a small particle size, and thus the increase in fine particles in the electrode due to particle cracking can be mitigated, thereby improving the life characteristics of the battery.

[0228] In one embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles by 1 μm to 18 μm.

[0229] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm smaller, 1.5 μm to 15 μm smaller, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.

[0230] When the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, for example, when the above range is satisfied, the single particles can have excellent particle strength even if they are formed with a small particle size, and thus the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, resulting in an improvement in the life characteristics and energy density of the battery.

[0231] According to a further embodiment of the present application, the single particles are contained in an amount of 15 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material. The single particles may be contained in an amount of 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0232] For example, the single particles may be included in an amount of 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more relative to 100 parts by weight of the positive electrode active material. The single particles may be included in an amount of 100 parts by weight or less relative to 100 parts by weight of the positive electrode active material.

[0233] When the single particles are contained in the above range, excellent battery characteristics can be exhibited in combination with the above-mentioned negative electrode material. In particular, when the single particles are 15 parts by weight or more, the increase in fine particles in the electrode due to particle cracking during rolling after electrode preparation can be mitigated, thereby improving the life characteristics of the battery.

[0234] In one embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the secondary particles may be 85 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 0 parts by weight or more relative to 100 parts by weight of the positive electrode active material.

[0235] When the above range is satisfied, the above-mentioned effect due to the presence of the single particle positive electrode active material can be maximized. When the secondary particle positive electrode active material is included, the component may be the same as or different from the components exemplified in the single particle positive electrode active material, and may refer to a form in which single particles are aggregated.

[0236] In one embodiment of the present application, the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and still more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0237] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.

[0238] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0239] The positive electrode binder plays a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0240] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be used selectively in a single layer or multilayer structure.

[0241] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0242] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0243] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0244] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these can be used more preferably.

[0245] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2- , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:

[0246] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0247] One embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system. EXAMPLES

[0248] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are intended to illustrate the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.

[0249] <Production Example> Example 1 Anode manufacturing Preparation of the first negative electrode active material layer A negative electrode slurry was prepared by adding Si (average particle size (D50): 5 μm) as a silicon-based active material, a second conductive material, a third conductive material, and polyacrylamide (PAM) as a water-based binder as a binder, and SBR as a rubber-based binder in a weight ratio of 89:0:1:4.5:5.5 to distilled water as a solvent for forming a negative electrode slurry (solid concentration 28 wt%).

[0250] The second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the third conductive material is carbon nanotubes.

[0251] As a specific mixing method, the second conductive material, the third conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the silicon-based active material was added and dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.

[0252] Preparation of second negative electrode active material layer A second negative electrode active material layer composition was prepared by mixing SiO (average particle size (D50): 6 μm) as a silicon-based active material, a second conductive material, a third conductive material, and polyacrylamide (PAM) as a water-based binder as a binder, and SBR as a rubber-based binder in a weight ratio of 80:9.5:0.5:10:0. The ... slurry was produced by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration 25 wt%).

[0253] The second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the third conductive material is carbon nanotubes.

[0254] As for the mixing method, the second conductive material, the third conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the active material was added and dispersed at 2500 rpm for 30 minutes to prepare a second negative electrode slurry.

[0255] The negative electrode slurry was applied to both sides of a copper current collector (thickness: 26 μm) at a rate of 87.7 mg / 25 cm. 2 and the second negative electrode slurry was applied to the first negative electrode active material layer at a loading amount of 20 mg / cm. 2 The coated negative electrode active material layer was then roll pressed and dried in a vacuum oven at 130° C. for 10 hours to form a first negative electrode active material layer (thickness: 41 μm) and a second negative electrode active material layer (thickness: 15 μm).

[0256] In Example 1, a negative electrode was prepared in which the first and second negative electrode active material layers had the compositions and contents shown in Table 1 below.

[0257] [Table 1]

[0258] For reference, Comparative Examples 1 to 3 in Table 1 are negative electrodes having a single layer structure in which the second negative electrode active material layer is not provided, that is, the negative electrodes have a single negative electrode active material layer, that is, the negative electrodes are prepared by applying only the first negative electrode active material layer slurry onto the negative electrode current collector layer and then drying it.

[0259] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).

[0260] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).

[0261] An electrolyte was injected between the positive electrode and the negative electrode of Example 1 via a polyethylene separator, to prepare the secondary battery of Example 1.

[0262] The electrolyte was an organic solvent made by mixing fluoroethylene carbonate (FEC) and diethyl carbonate (DMC) in a volume ratio of 10:90, to which vinylene carbonate was added at 3 wt% based on the total weight of the electrolyte, and LiPF6 was added as a lithium salt at a concentration of 1M.

[0263] Except for using the negative electrodes of the above-mentioned Examples and Comparative Examples, secondary batteries were fabricated in the same manner as described above.

[0264] Experimental example 1: Monocell life evaluation The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention rate. The secondary batteries were subjected to a cycle test at 4.2-3.0 V, 1 C / 0.5 C, and the number of cycles at which the capacity retention rate reached 80% was measured.

[0265] Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at 1st cycle)} x 100

[0266] The results are shown in Table 2 below.

[0267] Experimental example 2: Resistance increase rate measurement evaluation In the test of Experimental Example 1, the capacity retention rate was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at 2.5C pulse at SOC50, and the resistance increase rate was compared and analyzed.

[0268] In the resistance increase rate measurement evaluation, data at 150 cycles was calculated, and the results are shown in Table 2 below.

[0269] Experimental example 3: Rapid charging evaluation The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were charged at 6C in CC-CV mode (4.2V, 5% cut-off) at 35°C using an electrochemical charger / discharger at SOC20, and the charging time was measured. The results are shown in Table 2 below.

[0270] Experimental example 4: Electrode curl measurement The degree of warping was measured by placing the uncoated part of the coated electrode on top and measuring the height of the center as shown in Figure 5. In other words, when the binder dries, tensile stress acts on the coated part, causing it to dent, resulting in curling, and this experiment measured the degree of curling, and the results are shown in Table 2 below.

[0271] [Table 2]

[0272] As can be seen from Table 2, in the case of Examples 1 to 6 according to the present application, the first negative electrode binder includes the above-mentioned PAM-based or PAA-based polymer aqueous binder; and a rubber-based binder; and in particular satisfies the range of the above formula 1. That is, it was confirmed that the ratio of the aqueous binder for improving the dispersibility of the first negative electrode active material layer composition can be reduced and a rubber-based binder can be further included, and the problem of process stability in which shrinkage due to heat is deepened can be solved, and the life characteristics can be enhanced. In addition, it was confirmed that the use of the first negative electrode binder having the specific composition as described above improves volume expansion, reduces the amount of conductive material, and allows the electrode to be formed thinner, maximizing the capacity characteristics, and improving non-uniformity in the depth direction.

[0273] In addition, it was confirmed that the life and resistance performance were improved in Examples 1 to 6, which correspond to the cases where a second negative electrode active material layer was introduced, and further, in the cases of Examples 1 and 6, where the ratio of the second negative electrode active material in the second negative electrode active material layer was increased, the rapid charging performance was improved.

[0274] Furthermore, it was found by comparing Example 1 and Example 2 that the higher the ratio of the rubber binder, the less the curling phenomenon of the electrode occurs, which is advantageous for process stability.

[0275] In addition, when comparing Example 1 and Example 5, when the Si content of the first negative electrode active material layer is high, the thickness of the first negative electrode active material layer can be formed to be thin. In this case, as can be seen from the fast charging performance, it was confirmed that Example 1 has superior fast charging performance compared to Example 5. This is because the binder of the first negative electrode active material layer satisfies the combination according to the present application, and the first negative electrode active material layer can be formed to be thin.

[0276] The comparative examples 1 to 3 are comparative examples having a single layer as the negative electrode active material layer. Specifically, they are single layers, and correspond to the cases having only the first negative electrode active material layer according to the present application, having only a rubber-based binder, or having only a water-based binder. In these cases, it was confirmed that the life characteristics were deteriorated and the resistance increase rate was increased compared to the examples. This corresponds to the result of the irregular reaction on the surface of the silicon-based negative electrode.

[0277] In Comparative Examples 4 to 7, the negative electrode active material layer has a double layer structure formed with two layers like the Examples, but Comparative Example 4 corresponds to the case where the first negative electrode active material layer has only an aqueous binder, Comparative Example 5 corresponds to the case where the first negative electrode active material layer has only a rubber-based binder, Comparative Example 6 corresponds to the case where the range of Formula 1 is exceeded, and Comparative Example 7 corresponds to the case where the range of Formula 1 is exceeded.

[0278] In conclusion, in the case of Comparative Examples 4 to 7, the first negative electrode active material layer according to the present application does not satisfy the range of Formula 1, and it was confirmed that when the ratio of the present application is not satisfied, the life characteristics are deteriorated compared to Examples 1 to 6, and the resistance increase rate is also high.

[0279] Also, as can be seen from Tables 1 and 2, it was confirmed that the thickness of the first negative electrode active material layer is determined by the content of Si contained therein. Comparative Examples 1 to 3 correspond to a single layer structure that does not have a second negative electrode active material layer. Since SiO has a smaller capacity than Si, in order to obtain the same capacity, the thickness of all the negative electrode active material layers can be formed thinner than in the examples of the present application. As a result, the fast charging performance can be slightly superior to that of the examples, but as can be seen from Table 2, it was confirmed that the life characteristics are very inferior to that of the examples and the resistance increase rate is also high.

[0280] For reference, Comparative Examples 4 and 5 have the same silicon content and thickness range as Example 1 of the present application. In this case, as can be seen from Table 2, the fast charging performance is evaluated similarly to the examples, but when the first negative electrode active material layer according to the present application does not satisfy the range of Formula 1 and does not satisfy the ratio of the present application, it was confirmed that the life characteristics were significantly reduced and the resistance increase rate was also high. [Explanation of symbols]

[0281] 10...Second negative electrode active material layer 20...first negative electrode active material layer 30 Negative electrode current collector layer 40: Negative electrode active material layer including a first negative electrode active material layer and a second negative electrode active material layer

Claims

1. A negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a first negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a second negative electrode active material layer provided on a surface of the first negative electrode active material layer opposite to a surface facing the negative electrode current collector layer, the first negative electrode active material layer includes a first negative electrode active material layer composition including a first negative electrode active material, and the second negative electrode active material layer includes a second negative electrode active material layer composition including a second negative electrode active material, The first negative electrode active material is SiO x (x=0) and SiO x (0<x<2), based on 100 parts by weight of the first negative electrode active material, x (x=0) 95 parts by weight or more, The second negative electrode active material includes a mixture of at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of being alloyed with lithium, and a lithium-containing nitride, the first negative electrode active material layer composition includes a first negative electrode binder, The first negative electrode binder comprises a polymer aqueous binder including a PAM system or a PAA system; and a rubber-based binder; and satisfies the following formula 1: [Formula 1] 1≦X / Y<4 In the above formula 1, X is the weight part of the rubber-based binder based on 100 parts by weight of the first negative electrode binder, Y is the weight part of the aqueous binder based on 100 weight parts of the first negative electrode binder.

2. The silicon-based active material is SiO x 2. The negative electrode for a lithium secondary battery according to claim 1, comprising one or more selected from the group consisting of (0<x<2), SiC, and a Si alloy.

3. The silicon-based active material is SiO x (0<x<2); or SiC.

4. The negative electrode of claim 1 , wherein the silicon-based active material is present in an amount of 60 parts by weight or more based on 100 parts by weight of the second negative electrode active material.

5. 2 . The negative electrode of claim 1 , wherein the first negative electrode active material is 60 parts by weight or more based on 100 parts by weight of a first negative electrode active material layer composition.

6. The thickness of the first negative electrode active material layer is 10 μm or more and 200 μm or less, 2 . The negative electrode for a lithium secondary battery according to claim 1 , wherein the second negative electrode active material layer has a thickness of 10 μm or more and 100 μm or less.

7. The X is 50 parts by weight or more and 95 parts by weight or less, 2. The negative electrode for a lithium secondary battery according to claim 1, wherein Y is 5 parts by weight or more and 50 parts by weight or less.

8. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the first negative electrode active material layer composition further comprises at least one selected from the group consisting of a first negative electrode conductive material; and a first negative electrode binder.

9. the first negative electrode active material layer is formed on the entire surface of the negative electrode current collector layer, The negative electrode for a lithium secondary battery according to claim 1 , wherein the second negative electrode active material layer is formed on an entire surface of the first negative electrode active material layer.

10. Providing a negative electrode current collector layer; forming a first negative electrode active material layer by applying a first negative electrode active material composition to one or both surfaces of the negative electrode current collector layer; and forming a second negative electrode active material layer by applying a second negative electrode active material composition to a surface of the first negative electrode active material layer opposite to a surface facing the negative electrode current collector layer, the second negative electrode active material composition including a second negative electrode active material, The first negative electrode active material is SiO x (x=0) and SiO x (0<x<2), based on 100 parts by weight of the first negative electrode active material, x (x=0) 95 parts by weight or more, The second negative electrode active material includes a mixture of at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of being alloyed with lithium, and a lithium-containing nitride, the first negative electrode active material layer composition includes a first negative electrode binder, The first negative electrode binder includes a polymer aqueous binder including a PAM system or a PAA system; and a rubber-based binder; and satisfies the following formula 1: [Formula 1] 1≦X / Y<4 In the above formula 1, X is the weight part of the rubber-based binder based on 100 parts by weight of the first negative electrode binder, Y is the weight part of the aqueous binder based on 100 weight parts of the first negative electrode binder.

11. the first negative electrode active material layer is formed on the entire surface of the negative electrode current collector layer, The method for manufacturing a negative electrode for a lithium secondary battery according to claim 10 , wherein the second negative electrode active material layer is formed on an entire surface of the first negative electrode active material layer.

12. forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet on dry process; The wet-on-dry process includes: Applying a first negative electrode active material layer composition; partially or entirely drying the applied first negative electrode active material layer composition to form a first negative electrode active material layer; and applying the second negative electrode active material layer composition to the first negative electrode active material layer; The method for producing a negative electrode for a lithium secondary battery according to claim 10 or 11, comprising:

13. forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet-on-wet process; The wet-on-wet process includes: applying a first negative electrode active material layer composition; and applying the second negative electrode active material layer composition onto the first negative electrode active material layer composition while the first negative electrode active material layer composition is still wet; The method for producing a negative electrode for a lithium secondary battery according to claim 10 or 11, comprising:

14. Positive electrode; The negative electrode for a lithium secondary battery according to any one of claims 1 to 9; A separator disposed between the positive electrode and the negative electrode; and Electrolyte; A lithium secondary battery comprising:

Citation Information

Patent Citations

  • High-capacity-density lithium ion battery negative electrode

    CN111384370A

  • Negative electrode plate for secondary battery, and secondary battery, and battery pack

    JP2014035885A

  • Electronic device including protection member for display

    KR1020230140305A

  • Negative electrode slurry composition, and negative electrode and lithium battery including the negative electrode slurry composition

    US20160141624A1

  • Positive Electrode For Lithium Secondary Battery And Method For Manufacturing The Same

    US20190312259A1